Modified diglycolamides for the An(III) + Ln(III) co-separation: evaluation by solvent extraction and time-resolved laser fluorescence spectroscopy - Wilden, Andreas; Modolo, Giuseppe; Lange, Steve; Sadowski, Fabian; Beele, Björn B.; Skerencak-Frech, Andrej; Panak, Petra; Iqbal, Mudassir; Verboom, Willem; Geist, Andreas; Bosbach, Dirk (Solvent extraction and ion exchange, 2014)
The use of two recently developed diglycolamide-based extractants for the co-separation of trivalent actinides (An(III)) and lanthanides (Ln(III)) is described and compared to the well-known extractant TODGA (N,N,N’,N’-tetraoctyl diglycolamide). The addition of one or two methyl groups to the central methylene carbon atoms of the TODGA molecule leads to a reduction of the extraction efficiency for An(III) and Ln(III). This is attributed to a lower complex formation constant, which was proven by Time-Resolved Laser Fluorescence Spectroscopy (TRLFS). Conditional stability constants were determined by solvent extraction and TRLFS. The reduction in extraction efficiency leads to overall reduced distribution ratios of all tested metal ions, including Sr(II). The reduced Sr(II) extraction is beneficial as a co-extraction in a solvent extraction process could be avoided, while an efficient extraction of the desired An(III) and Ln(III) is still achieved. Furthermore, this might be a benefit, as the stripping behavior might be improved, even at moderate nitric acid concentrations. The slightly higher affinity of the diglycolamides towards Eu(III) over Am(III) is represented by all ligands, although the selectivity is rather low. This results in promising extraction properties of the modified diglycolamides towards the development of continuous solvent extraction processes.
Gesehen am 23.09.2020